1998
DOI: 10.1038/31933
|View full text |Cite
|
Sign up to set email alerts
|

The ParaHox gene cluster is an evolutionary sister of the Hox gene cluster

Abstract: Genes of the Hox cluster are restricted to the animal kingdom and play a central role in axial patterning in divergent animal phyla. Despite its evolutionary and developmental significance, the origin of the Hox gene cluster is obscure. The consensus is that a primordial Hox cluster arose by tandem gene duplication close to animal origins. Several homeobox genes with high sequence identity to Hox genes are found outside the Hox cluster and are known as 'dispersed' Hox-like genes; these genes may have been tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
395
1
4

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(412 citation statements)
references
References 25 publications
12
395
1
4
Order By: Relevance
“…Although some if not all cnidarians possess a limited number of bilaterian-like anterior hox genes, many of these genes are paralogs and they do not represent equivalents of the hox cluster (Chourrout et al, 2006;Kamm et al, 2006). One hypothesis is that hox/parahox clusters originated from the duplication of an ancient protohox cluster with anterior and posterior hox/parahox genes (Brooke et al, 1998;Ferrier and Holland, 2001;Brooke and Holland, 2003;Garcia-Fernandez, 2005a, b). However, other findings propose the protohox cluster may have only consisted of two anterior genes, while the non-anterior genes most probably appeared independently in the hox and parahox clusters after the separation of bilaterians and cnidarians (Chourrout et al, 2006;Kamm et al, 2006).…”
Section: An Ancient Function Of Wnt Signalling In Axial Patterningmentioning
confidence: 99%
“…Although some if not all cnidarians possess a limited number of bilaterian-like anterior hox genes, many of these genes are paralogs and they do not represent equivalents of the hox cluster (Chourrout et al, 2006;Kamm et al, 2006). One hypothesis is that hox/parahox clusters originated from the duplication of an ancient protohox cluster with anterior and posterior hox/parahox genes (Brooke et al, 1998;Ferrier and Holland, 2001;Brooke and Holland, 2003;Garcia-Fernandez, 2005a, b). However, other findings propose the protohox cluster may have only consisted of two anterior genes, while the non-anterior genes most probably appeared independently in the hox and parahox clusters after the separation of bilaterians and cnidarians (Chourrout et al, 2006;Kamm et al, 2006).…”
Section: An Ancient Function Of Wnt Signalling In Axial Patterningmentioning
confidence: 99%
“…Recently, data from experimental models and gene expression profiling in patients with acute myeloid leukemia (AML) have identified CDX2 as a powerful oncogene when aberrantly expressed in adult hematopoietic progenitor cells: [6][7][8] the 'caudal related homeobox gene' CDX2 belongs to the family of so-called 'ParaHox genes', which also includes CDX1, CDX4 and the GSH2 homeobox gene. 9 Normally expression of CDX2 is tightly regulated in the adult organism, with expression in the intestine but no expression in adult hematopoietic tissue. 10 It was shown that CDX2 is among the most frequent aberrantly expressed proto-oncogenes in AML, with up to 89% of AML cases with normal karyotype expressing CDX2.…”
Section: Introductionmentioning
confidence: 99%
“…The gene encoding Pdx1 (Pdx1) is a central member of a mammalian Parahox gene cluster on mouse chromosome 5. This cluster is so-named because it represents a group of developmentally important genes in mammals that is found outside the classical Hox (homeobox) cluster of genes [10]. The Parahox cluster is comprised of three genes, Gsh1, Pdx1, and Cdx2/3, all of which are expressed in specific pancreatic cell types [11].…”
Section: Introductionmentioning
confidence: 99%